The Role of (Geoelectric and Hydrogeologic) Parameters in the Evaluation of Groundwater reservoir at South of Jabal Sinjar area. - Alridha, Nawal; Al-Yasi, Ameen; AL-Khafaji, Wadhah (Iraqi Journal of Science, 2023)
In this study the (geoelectric – hydrogeologic) parameters which are obtained by thequantitative interpretation of (80) Schlumberger Vertical Electrical Sounding (VES)points distributed in six linear profiles within the study area are used in addition to(6) pumping test locations for the groundwater reservoir located to the south of JabalSinjar (Sinjar anticline). The studied area covers about 7920Km2. The (VES) fieldreadings were interpreted manually by using the auxiliary point method-partialresistivity curve matching,then the interpreted results enhanced by using computersoftware specialized for the 1D- (VES) resistivity curves interpretation. The (VES)results analyzed by using modern techniques in order to construct a new predictedhydrogeologic maps through the application of an empirical statistical relationsbetween geoelectric and the Hydraulic parameters. The results of empirical relationsrepresent the predicted hydraulic parameters for the points where no pumping testsachieved. The results represents the predicted hydraulic conductivity (K),Transmissivity(Tr), Specific capacity(Sc) and Total Dissolved Solids (TDS). Acomputer software used to display the results as maps to display the calculatedhydrogeologic parameters variation across the studied area. This result helps todelineate the most productive and good quality groundwater within the study area.